Investor and (Value Line) Analyst Underreaction to Information about Future Earnings: The Corrective Role of Non‐Earnings‐Surprise Information - Shane, Philip; Brous, Peter (Journal of Accounting Research, 2001)
Prior research suggests that financial analysts’ earnings forecasts and stock prices underreact to earnings news. This paper provides evidence that analysts and investors correct this underreaction in response to the next earnings announcement and to other (non‐earnings‐surprise) information available between earnings announcements. Our evidence also suggests that analysts and investors underreact to information reflected in analysts’ earnings forecast revisions and that non‐earnings‐surprise information helps correct this underreaction as well. Controlling for corrective non‐earnings‐surprise information significantly increases estimates of the degree to which analysts’ forecasting behavior can explain drifts in returns following both earnings announcements and analysts’ earnings forecast revisions.